PENINGKATAN KEMAMPUAN KREATIVITAS SENI MELALUI PEMBELAJARAN FINGER PAINTING PADA KELOMPOK B DI RA SHALAHUDDIN BLAYU WAJAK-MALANG - Husniatul Ilmi; Ratih Permata Sari (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2024)
Artistic creativity is one of the most important aspects in a child's development. Therefore, it requires a fun learning concept, namely finger painting. The purpose of the study was to describe the form and results of increasing artistic creativity abilities through finger painting learning. The research methodology used was classroom action research with a mix-method research type. As well as, data collection techniques, including observation, interviews, and documentation. Data analysis was carried out based on data obtained in each cycle. The results of the study and discussion showed that children's artistic creativity is able to train exploration in making clear visualization patterns of image shapes. The results of the study of artistic creativity in cycle I reached 69.67%. Meanwhile, artistic creativity in cycle II reached 84.09% through finger painting learning using poster paint colors, color caryons, food colors, mixing color porridge and food colors, pencil strokes, and color sprays. Here, children will be introduced to techniques that use hands and without hands. This means that researchers instruct them to use brushes, color sprays, and pencils to create image patterns. The conclusion of the study is that finger painting learning can help children improve their skills in the field of artistic abilities by making clear image patterns and colors. Thus, training children's basic skills from an early age will be a provision in the development period such as understanding the shape of the picture pattern visually. Finger painting learning can explore aspects of child development and is very suitable to be introduced at the sensory motor age level in children.